Exploratory Analysis of Financial literacy for College Students - Yenni Martok (Journal of Accounting and Management Innovation, 2021)
The purpose of this research is to know the importance of financial literacy education for college students. The research method is using library research. From the discussion, it can be concluded that financial literacy is important for students to manage their personal finance.  College is a unique time in a young person’s life. After they have graduated from college, they are going to have their own life for the first time. Personal finance resources will affect major decisions shortly after graduation. Student’s experience in handling money will bring them to the positive influence of financial literacy. Knowledge of financial management helps to solve money problems, such as saving, budgeting, investment, managing debt,   and consumptions decision. The level of financial literacy will lead to money decision-making. It also includes the decision-making in the management of the emergency funds and financial goals. Effective money management will affect personal life.Keyword: Financial Literacy, Personal Finance, Money Management